1997
DOI: 10.1002/jhet.5570340316
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazo[1,2‐c]quinazoline dimers as potential antitumor agents

Abstract: The 6‐substituted benzimidazo[1,2‐c]quinazoline 1 is a lead structure from our DNA intercalator program and is cytotoxic to the human colon cancer tumor line HT‐29 with an inhibitory concentration 50, IC50 of 4.00 μM. In order to try and improve the limited cytotoxicity of this class of compound we prepared a series consisting of two benzimidazo[1,2‐c]quinazoline moieties linked by a polyalkylamino bridge, of different length and substitution. The compound with the ‐NH‐(CH2)3‐N(CH3)‐(CH2)3‐NH‐bridge had an inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…7 Benzo[4,5]imidazo[1,2- c ]quinazoline is a trinitrogen heterocycle that hosts both the fused structure of benzimidazole and quinazoline via a shared bond. 8 The combination of benzimidazole and quinazoline frameworks, benzimidazoquinazoline derivatives, are valuable substrates with different biological activities as shown in Figure 1 and benzoimidazo[1,2- c ]quinazoline derivatives exhibit wide spectrum of therapeutic activities such as antimicrobial, 9 antitumor, 10 anticancer, 11 antiviral, 12 anti-inflammatory, 13 and anticonvulsants. 14 Due to the remarkable importance of these molecules, we planned to propose a new method for construction of benzoimidazo[1,2- c ]quinazoline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…7 Benzo[4,5]imidazo[1,2- c ]quinazoline is a trinitrogen heterocycle that hosts both the fused structure of benzimidazole and quinazoline via a shared bond. 8 The combination of benzimidazole and quinazoline frameworks, benzimidazoquinazoline derivatives, are valuable substrates with different biological activities as shown in Figure 1 and benzoimidazo[1,2- c ]quinazoline derivatives exhibit wide spectrum of therapeutic activities such as antimicrobial, 9 antitumor, 10 anticancer, 11 antiviral, 12 anti-inflammatory, 13 and anticonvulsants. 14 Due to the remarkable importance of these molecules, we planned to propose a new method for construction of benzoimidazo[1,2- c ]quinazoline derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cyclic guanidines have also been employed as synthetically useful organocatalysts and reagents in organic synthesis . Quinazoline-containing cyclic guanidines such as II and III (Figure ) are highly potent virucidal and neoplasm inhibitors and are found to be active against breast cancer …”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, a wide variety of transition metals, such as Cu, Pd, Zn, Ru, Ir and Au, has been employed proficiently for the formation of C–N bonds, as they trigger the formation of many nitrogen atom-containing scaffolds in organic molecules. Perceiving the significance of C–N bond formation, Chao Li et al have reported a copper-catalyzed domino process for the synthesis of benzimidazo­[1,2- a ]­quinazoline derivatives, a pharmaceutically interesting fused scaffold containing both the quinazoline and benzimidazole entities (Figure ). They employed an Ullmann C–N bond formation followed by two bond cleavages through an intermediate 3-(1 H -benzo­[ d ]­imidazole-2-yl)-2-(2-bromophenyl)-2,3-dihydroquinazoline-4­(1 H )-one by choosing N -(2-benzimidazolyl)-2-aminobenzamide and 2-halogenated benzaldehydes as their leading substrates. An extensive literature survey reveals that the synergistic unification of the quinazoline and benzimidazole scaffold can result in the fabrication of novel compounds with improved efficiency. Consequently, several attractive approaches to construct quinazoline-fused benzimidazoles have been reported. …”
Section: Introductionmentioning
confidence: 99%